Psychological and pedagogical support of tourist travel as a process of familiarization with the civilizational heritage - Kuznetsova, N.V.; Suleimen, S.B.; Arpentieva, M.R.; Kassymova, G.K.; Xu, Wenxin; Fang, Yuqi (Geomedia Majalah Ilmiah dan Informasi Kegeografian, 2024)
The study of tourism psychological and educational issues and the development and implementation of tourism psychological and educational support are still an area of relatively little theoretical and applied research. At the same time, tourism is not just a leisure activity, but a transformative experience that can profoundly change personal and social identity, serve the development of the individual, and change the needs of the individual as a "traveller." This shift not only affects the tourism industry itself, but also creates positive changes in the training of tourism personnel. Therefore, modern family and youth tourism is undergoing positive changes in both form and content.This study aims to analyze the identity transformation of travelers when they come into contact with civilizational heritage, including regional heritage. The research method adopts a theoretical analysis of the identity transformation of travelers in the context of contact with civilizational heritage. In addition, there is a group of people who see travel as a way out of their problems, so their transformation may not be so obvious, but travel teaches them to believe in themselves and life, to accept challenges and uncertainties, to endure difficulties, and to accept change. Travel helps individuals redefine their identity in line with their own inner needs and desires rather than catering to external expectations.